Entre o peixe e o dendê; etnoecologia do povo dos Marimbús (Chapada Diamantina - BA) - Moura, Flávia de Barros Prado (Universidade Federal de São Carlos, 2002)
This study documents traditional ecological knowledge by a human population living in Chapada Diamantina, Northeast Brazil. The field work was carried out from June 1998 to May 1999 and included: open-ended interviews, structured interviews, direct observation, questionnaires and tours guided by fishermen. Fish and plants species were collected and taxonomically identified. The consistence of fishermen´s knowledge was observed through compared cognition tables. Local knowledge related to spatiotemporal distribution of fish, ethology, feeding behavior and fish reproduction are fundamental for fishing activities. Plant use is extensive: 131 species of plants medicinally, 69 species for food, 44 for firewood, 38 for house building, and 23 for fishing practices. 72 products from 52 species of animals were reported to be used for prevention and cure 40 physically or spiritually derived illnesses. Most of the medicines (55 %) are derived from by-products of animals normally hunted for food intention. Traditional knowledge about fish species was gathered and proved to be consistent with data from scientific literature. Local knowledge is fundamental for fishing activities and should be taken into account in the planning of sustainable management for the area, which has been set aside by government as an APA (Environmental Protection Area).
Keywords: Ecologia humana; Etnoecologia; Etnoictiologia; Chapada Diamantina; Medicina popular; Recursos botânicos; Ethnoecology; Ethnoichthyology; Chapada Diamantina; Folk medicine; Botanical resources; CIENCIAS BIOLOGICAS::ECOLOGIA